2012
DOI: 10.1163/092050611x580463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of EGF and bFGF on Fibroblast Proliferation and Angiogenic Cytokine Production from Cultured Dermal Substitutes

Abstract: Growth factors accelerate wound healing but the underlying mechanisms remain poorly understood. The aim of this study was to investigate the effect of epidermal growth factor (EGF) and basic fibroblast growth factor (bFGF) on fibroblast proliferation and production of angiogenic factors from cultured dermal substitutes (CDS). In the first experiment, fibroblasts were seeded into a flask at a density of 1 × 10(4) cells/cm(2).Cell proliferation was assessed after culturing in media containing EGF or bFGF at conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 25 publications
2
40
0
Order By: Relevance
“…The effect of EGF on increased cell proliferation and mitosis has been reported. 9,14,39 Also, gelatin increased cell proliferation in the hybrid scaffolds as mentioned before. Therefore, the PLGA and hybrid scaffold were selected for the microscopic and histological analyses.…”
Section: Blood Clotting and Platelet Adhesionsupporting
confidence: 69%
“…The effect of EGF on increased cell proliferation and mitosis has been reported. 9,14,39 Also, gelatin increased cell proliferation in the hybrid scaffolds as mentioned before. Therefore, the PLGA and hybrid scaffold were selected for the microscopic and histological analyses.…”
Section: Blood Clotting and Platelet Adhesionsupporting
confidence: 69%
“…In a previous study [28], we reported that fibroblast proliferation was facilitated in a flask containing culture medium with bFGF ranging from 2 to 10 µg/15mL, but failed to facilitate proliferation at 50 µg/15mL. On the other hand, fibroblast proliferation was facilitated in a flask containing culture medium with EGF ranging from 2 to 50 µg/15mL.…”
Section: Discussionmentioning
confidence: 89%
“…[16] Briefly, fibroblasts (cell line derived from human dermis) were suspended in double concentrated Dulbecco's modified Eagle's medium supplemented with 20% fetal bovine serum at a density of 80 × 10 5 cells/12 mL. Fibroblast suspension (12 mL) was mixed with sterilized 1% Col solution (12 mL) at a temperature below 10°C.…”
Section: Experiments In Vitromentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] We have developed several types of wound dressing composed of hyaluronic acid (HA) and collagen (Col) spongy sheet containing epidermal growth factor (EGF). [14][15][16][17] Both HA and Col have the potential to facilitate wound healing. In the development of anti-adhesive products, researchers have focused on preventing surgically excised tissue from adhering to surrounding tissues using mechanical barriers such as membranes and spongy sheets.…”
Section: Introductionmentioning
confidence: 99%